Comparison of fentanyl and dexmedetomidine as an adjuvant to bupivacaine for unilateral spinal anesthesia in lower limb surgery: a randomized trial - Taher-Baneh,Naseh (2019)
Abstract Background and objectives One of the disadvantages of unilateral spinal anesthesia is the short duration of post-operative analgesia, which can be addressed by adding adjuvants to local anesthetics. The aim of current study was to compare the effects of adding dexmedetomidine, fentanyl, or saline to bupivacaine on the properties of unilateral spinal anesthesia in patients undergoing calf surgery. Methods In this double-blind clinical trial, 90 patients who underwent elective calf surgery were randomly divided into three groups. The spinal anesthetic rate in each of the three groups was 1 mL bupivacaine 0.5% (5 mg). In groups BD, BF and BS, 5 µg of dexmedetomidine, 25 µg of fentanyl and 0.5 mL saline were added, respectively. The duration of the motor and sensory blocks in both limbs and the rate of pain during 24 h after surgery were calculated. Hemodynamic changes were also measured during anesthesia for up to 90 min. Results The duration of both of motor and sensory block was significantly longer in dependent limb in the BF (96 and 169 min) and BD (92 and 166 min) groups than the BS (84 and 157 min) group. Visual Analog Scale was significantly lower in the two groups of BF (1.4) and BD (1.3), within 24 h after surgery, than the BS (1.6) group. Conclusions The addition of fentanyl and dexmedetomidine to bupivacaine in unilateral spinal anesthesia can increase the duration of the motor and sensory block in dependent limb and prolong the duration of postoperative pain. However, fentanyl is more effective than dexmedetomidine.